Penyuluhan Hidup Berkah Tanpa Riba Pada Jama’ah Muslim Pedesaan - Saepudin, Ahmad (STIE Syariah Indonesia Purwakarta, 2022)
Blessing life is a very coveted part for Muslims, blessing can be addressed through the form of endeavor in fulfilling the needs of physical life which in its endeavor must refer to what is commanded by Allah SWT. One of the things to achieve the value of life that is blessed by a Muslim in mu'amalah activities must be based on the Qur'an, Hadith and Ijma ulama, including transactions in mu'amalah activities must get out of the false path. False transaction activities are still found in rural Muslims in Cibinong and Jatiluhur Purwakarta, such as borrowing and borrowing money using the services of moneylenders. This PKM program aims to provide a material understanding of Riba, starting from the understanding according to the scholars, the legal basis of usury, the types / types of usury, the reasons for the prohibition of usury and the impact of usury on life. This PKM method uses a lecture and discussion approach. The results of the PKM on counseling on blessed life without usury to rural Muslim congregations in Cibinong Village and Jatitimekar Village, Jatiluhur District, Purwakarta Regency went well and smoothly, it was seen that the participants really enjoyed and listened to this counseling program well, because the counseling material was delivered clearly and straightforwardly. The response of the congregations of the ta'lim assembly was also good, although there was one congregation who felt offended about loan sharks, in the end the congregation wanted to move or leave the practice of moneylenders. With this outreach program, the community feels enlightened, especially the problem of usury practice which is rarely conveyed at the recitation, and the congregation of the ta'lim assembly also knows our tips for achieving a blessed life without usury.